"Understanding retail layout: a case study at Agrobazaar Rakyat 1Malaysia Simpang Renggam, Johor" / Hamizah Mohd Sanif - Mohd Sanif, Hamizah (2018)
The roles of retailers in the business market have seen to be important in our daily life. One of the common things between them is arranged display of their products more favor than untidy display. Even so, many retailers do not have necessary knowledge in arranging the products based on the customers' preferences (Pizzi and Scarpi, 2016).